Local Government Unit Synergy for Reyog Ponorogo Sustainability - Ardhana Januar Mahardhani; Romadona Desy Suciati; Laela Rosidha; Restu Mufanti (International Journal of Research and Community Empowerment, 2026)
The continuity of Reyog art in Ponorogo Regency cannot be understood from a single perspective, but must be examined through various interrelated social, cultural, and institutional dimensions. This study focuses on analyzing the patterns of collaboration among key actors in sustaining the existence of Reyog art in Ponorogo Regency. The method used to answer this problem is qualitative, with the research object being the local government and the existence of other actors who have an influence on the development of Reyog Ponorogo art, such as professional organizations, media, universities, and small and medium entrepreneurs. The research results show that actor collaboration is needed in the development of Reyog Ponorogo art in an effort to maintain its sustainability. Collaboration process the penthahelix model has actually been implemented in the development of Reyog Ponorogo art, namely involving academics, business, community, government and media. In conclusion enhancing cooperation among local government entities and promoting organized partnerships with outside stakeholders are vital approaches to guarantee the enduring sustainability of Reyog Ponorogo as a cultural legacy and a catalyst for the local creative economy. This study offers actionable insights for enhancing policy integration and cross-sector collaboration frameworks that promote sustainable cultural management in line with the Sustainable Development Goals (SDGs).